THE GUARANTEE OF THE RIGHT TO THE PERSONALITY OF INTIMACY THROUGH THE FREEDOM OF DIGITAL PRESS: REFLECTIONS ON THE DIGNITY OF DEFENDERS AFTER COMPLIANCE WITH THE PENALTY OR ABSOLVING (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Considering the viralization and feedback power of information indexing sites on the Internet, this article reflects and investigates the guarantee to defendants who have already served their sentences in criminal proceedings, or who have been absolved of them, to the right to be forgotten. , referring to the constitutional right of the personality, in the sense that it can regenerate itself and continue, in a dignified way, with its lives, without the ax or stigma resulting from the criminal action to which it responded. The controversy, which was found to exist even today in the Courts, is limited to the battle between the right to freedom of the press and veto to censorship, and on the other hand, the right to privacy, to oblivion. Through jurisprudential research it was found that the analysis is necessary on a case by case basis, weighing such constitutional values, in order to decide which one should prevail.